INDEPENDENT CAMPUS POLICY IN THE NEW NORMAL ERA - Muhammad Qorib; Rizka Harfiani (Proceeding International Seminar of Islamic Studies, 2021)
The independent campus policy is a government policy in Indonesian universities in implementing the education system. The purpose of this study was to analyze the independent campus policy in the new normal era, after going through the Covid-19 pandemic. The research approach is descriptive qualitative, with a research library type. The data collection technique used is documentation, which is collecting data from books, articles, journals, and so on. The data analysis technique used is content analysis. The results of the study describe four independent campus policies; first, namely the granting of autonomy for Tertiary Education Institutions to establish or open new study programs (with stipulated conditions); second, implementing an automatic re-accreditation program; third, giving freedom for universities Public Service Bodies and Work Units to become universities Legal Entities, and fourth, giving students the right to take courses outside the study program and changing the definition of semester credit units (credits). The hope of the success of the programs set by the government and universities is to improve the quality of graduates so that they are useful for the country, nation, religion and state.